Soil compaction and the architectural plasticity of root systems - Correa, José; Postma, Johannes A.; Watt, Michelle; Wojciechowski, Tobias (Journal of experimental botany, 2019)
Soil compaction is a serious global problem, and is a major cause of inadequate rooting and poor yield in crops around the world. Root system architecture (RSA) describes the spatial arrangement of root components within the soil and determines the plant’s exploration of the soil. Soil strength restricts root growth and may slow down root system development. RSA plasticity may have an adaptive value, providing environmental tolerance to soil compaction. However, it is challenging to distinguish developmental retardation (apparent plasticity) or responses to severe stress from those root architectural changes that may provide an actual environmental tolerance (adaptive plasticity). In this review, we outline the consequences of soil compaction on the rooting environment and extensively review the various root responses reported in the literature. Finally, we discuss which responses enhance root exploration capabilities in tolerant genotypes, and to what extent these responses might be useful for breeding. We conclude that RSA plasticity in response to soil compaction is complex and can be targeted in breeding to increase the performance of crops under specific agronomical conditions.